Advances in electrochemical sensors based on nanomaterials for the detection of lipid hormone - Zhang, Tingting; Du, Xin; Zhang, Zhenguo (Frontiers in Bioengineering and Biotechnology, 2022)
Lipid hormone is produced by highly differentiated endocrine cells and directly secretes into the blood circulation or tissue fluid to act as information transmission. It influences the physiological functions of the human body by controlling the metabolic processes of multiple tissue cells. Monitoring the levels of lipid hormone is of great importance for maintaining human health. The electrochemical sensor is considered as an ideal tool to detect lipid hormone owing to its advantages such as quick response, convenience and low economic costs. In recent three years, researchers have developed various electrochemical sensors for the detection of lipid hormone to improve their sensitivity or selectivity. The use of nanomaterials (such as carbon nanomaterials, precious metal and polymer) is a key research object and a breakthrough for improving the sensing performance of electrochemical sensors for detection of lipid hormone. This paper reviews and discusses the basic principle, nanomaterials, actuality and future development trend of electrochemical sensors for the detection of lipid hormone in the past three years.